Coupled Heat Transfer Inside a Thick‐Walled Structure With an Inner Open Cavity: A Numerical Approach - Salma Parvin; Md. Mazidul Islam; A. K. Azad; Afroza Akter (Engineering Reports, 2025)
ABSTRACT This research presents numerical modeling by investigating the coupled heat transfer of conduction and free convection phenomena within a thick‐walled square enclosure. This analysis aims to insert an open cavity barrier into the enclosure to reduce the natural convection effect and compare it with the empty enclosure. The top of the inner cavity is open and connected to the enclosed ceiling. The presence of the internal open cavity leads to alterations in convection patterns, resulting in diminished flow and the creation of a confined fluid compartment at the enclosure core. Consequently, this arrangement drops the local Nusselt number (Nul) along the hot interface boundary, reducing heat flux through the enclosure. The mathematical model is solved using the penalty approach of the Finite Element Method (FEM). The impact on thermal and flow behavior has been discussed for varying internal cavity dimensions (l/L = 0, 0.1, 0.3, 0.5), Rayleigh numbers (Ra = 103, 104, 105, 106), and a wall thickness (W = 0.05, 0.1, 0.15, 0.2). Clay brick's thermal property is used in the wall, and air is the heat transfer fluid. The numerical model was validated with a benchmark problem from the literature, accompanied by grid independence tests, demonstrating strong agreement with previously published studies. The outcomes reveal that the average Nusselt number was reduced up to 65.6% at Ra = 106 as a result of the inclusion of an inner cavity (l/L = 0.5), highlighting a notable decrease in heat transfer with increasing cavity size. In addition, the average Nusselt number drops up to 31.5% at Ra = 106 and W = 0.1. This research provides significant insights relevant to the design of energy‐efficient building envelopes, drying technologies, and process industry systems, especially with the optimization of hollow masonry bricks.